THE EFFECT OF VEHICLE VOLUME ON THE LEVEL OF ROAD DAMAGE IN RIGID PADDING: PENGARUH VOLUME KENDARAAN TERHADAP TINGKAT KERUSAKAN JALAN PADA PENGKERASAN RIGID - Sabta Habib Pasaribu (UPMI Proceeding Series, 2023)
The research aims to determine the effect of vehicle volume on the level of road damage on rigid paving. Medan, which is the capital of North Sumatra province, has sufficient road access with asphalt, concrete and lots of it. With some road pavements, namely asphalt concrete pavement. These roads are classified into several road classes, namely, class I roads which are inter-city roads, inter-provincial roads, arterial roads, class II roads which are collector roads and class III roads which are local roads in Medan. This data was obtained from the Medan City Bina Marga Service. The data required includes the length and width of the road, number of sections, median, number of road lanes and their completeness. The results of the vehicle volume study and road damage values ​​were analyzed using nonlinear multiple regression. The variables used are vehicle types which are grouped into light variables as variable X1, heavy vehicles as variable X2, and road damage value as variable Y. The analysis was carried out using the SPSS application. From the results above, it can be seen in the third row after variables X3 and X4 are removed. The calculated F is 2029.857. By comparing the calculated F with the F table α 0.05 with a degree of freedom in the numerator of 2 and a degree of freedom in the denominator of 3, we get an F table of 5,570. F count is greater than F table, meaning it shows that it is significant. By looking at the probability (Sig) which is smaller than the significance level (0.002 < 0.05), it can be concluded that the equation model Y = a X1 + b X2 + C is acceptable. From the results of the research conducted, it can be concluded that light vehicles and heavy vehicles have an influence on road damage on rigid pavement by 99.6%, while 0.6% is influenced by other variables outside this research and which were not examined by researchers. The road damage value is the total amount of each damage value on a road section. The road damage value (Nr) is the total amount of each damage value on each road section. The calculation method starts from data on the dimensions of road damage which is calculated into area units which are then compared. With the area of ​​the road being reviewed. Then the comparison results will appear in percentage form.